THE IMPACT OF ECONOMIC INFRASTRUCTURE INVESTMENT ON FOREIGN TRADE FLOWS: THE CASE OF SOUTH AFRICA - Nomfundo Portia Vacu-Ngqila (Oradea Journal of Business and Economics)
A well-functioning economic infrastructure is fundamental for sustainable economic growth in both developing and developed countries. It can be an effective tool for addressing economic and socioeconomic challenges and improving a country’s competitiveness. It is therefore critical to understand how economic infrastructure investment affects different aspects of economic growth. This would assist policymakers in ensuring that there is proper alignment between policies on infrastructure development and policies pertaining to economic development. Although many studies have been conducted on the impact of infrastructure development on economic development, literature focusing on the foreign trade aspect is scant. This study, therefore, bridges this gap by examining the impact of economic infrastructure investment on foreign trade flows in South Africa in the long run and short run. To examine this linkage, the study applied the autoregressive distributed lag (ARDL) bounds test on annual data for the period 1986 - 2022 and estimated two models. Model 1 investigates whether economic infrastructure investment has a significant impact on exports, while Model 2 examines the impact of economic infrastructure investment on imports. The findings of the study confirmed that economic infrastructure investment has a positive impact on exports both in the long run and short run, while it has no significant impact on imports. On the control variable, the findings confirmed that economic growth only has a long-run positive impact on exports, while it has a long-run and short-run positive impact on imports. It was found that trade openness and real effective exchange rates have positive effects on foreign trade flows regardless of the proxy used. The results confirmed that human capital has a negative effect on exports in the long run and short run, while it only has a positive long-run impact on imports. Furthermore, the findings show that money supply does not affect exports, while it negatively drives imports both in the long run and short run. Based on the main findings, the study recommends that governments should design policies that support investment in improving the country’s geographical conditions and connectivity. Furthermore, it is recommended that the South African government should prioritize the establishment and maintenance of functional economic infrastructure to create a conducive environment for local productivity and exports.